Information technology for mobile perimeter security systems creation - Lobanchykova, N; Kredentsar, S; Pilkevych, I; Medvediev, M (Journal of physics. Conference series, 2021)
The main aim of this research is the creation of information technology for mobile (of rapid deployment) security systems of the area perimeter. This system appears to be a complex of models and methods, information, software, and hardware mean that have interacted with users during decision-making and control of implementation for management solutions. The proposed information technology aimed at improving the protection level for security departments by automating the process of danger detection for perimeters and decision-making for alarm. The structural model of the system, the model of the system's components interaction, and the model of identifying the subjects of emergency threats have been proposed. A method for identifying unauthorized access to the perimeter of the secure facilities, using the production model of knowledge representation, was created. It is a set of linguistic expressions (such as "IF-THEN") and the knowledge matrix. The method of ranking for objects, which are threats of unauthorized access to the perimeter for secure facilities, has been proposed. The practical value of work consists of the possibility of the use of this information technology by perimeter's security systems of various objects. Proposed models are complete and suitable for hardware and software implementation.